Microsoft SQL Server 2012 unleashed - Rankins, Ray (Sams, 2013)
Buy the print version of¿ Microsoft SQL Server 2012 Unleashed and get the eBook version for free! eBook version includes chapters 44-60 not included in the print. See inside the book for access code and details. ¿ With up-to-the-minute content, this is the industry's most complete, useful guide to SQL Server 2012. ¿ You'll find start-to-finish coverage of SQL Server's core database server and management capabilities: all the real-world information, tips, guidelines, and samples you'll need to create and manage complex database solutions. The additional online chapters add extensive coverage of SQL Server Integration Services, Reporting Services, Analysis Services, T-SQL programming, .NET Framework integration, and much more. ¿ Authored by four expert SQL Server administrators, designers, developers, architects, and consultants, this book reflects immense experience with SQL Server in production environments. Intended for intermediate-to-advanced-level SQL Server professionals, it focuses on the product's most complex and powerful capabilities, and its newest tools and features. Understand SQL Server 2012's newest features, licensing changes, and capabilities of each edition Manage SQL Server 2012 more effectively with SQL Server Management Studio, the SQLCMD command-line query tool, and Powershell Use Policy-Based Management to centrally configure and operate SQL Server Utilize the new Extended Events trace capabilities within SSMS Maximize performance by optimizing design, queries, analysis, and workload management Implement new best practices for SQL Server high availability Deploy AlwaysOn Availability Groups and Failover Cluster Instances to achieve enterprise-class availability and disaster recovery Leverage new business intelligence improvements, including Master Data Services, Data Quality Services and Parallel Data Warehouse Deliver better full-text search with SQL Server 2012's new Semantic Search Improve reporting with new SQL Server 2012 Reporting Services features Download the following from informit.com/title/9780672336928: Sample databases and code examples ¿ ¿